GAMIFIKASI DALAM PdPR: INTEGRASI TEKNOLOGI MENGGUNAKAN QUIZZIZ (Practitioner Research, 2022)
Home-based teaching and learning (PdPR) is one of the alternatives chosen by the Ministry of Education Malaysia to replace face-to-face schooling as an initiative to prevent dropouts in education. PdPR is implemented when students are unable to attend school due to the Covid-19 pandemic that has hit the world beginning in early 2020. The purpose of this study is to identify the level of interest and readiness of students to accept the use of gamification methods during PdPR using Quizizz. A descriptive quantitative study design applying a survey method is used to obtain information from 128 Form One students in a secondary school in Kedah selected by using a purposive sampling technique. Data were collected through a questionnaire adapted from a previous study and containing 16 items. The research instrument has a high-reliability value that is between the range of 0.74 to 0.85. Data were analyzed using descriptive statistics namely frequency and percentage. The level of interest and willingness of students to accept the use of gamification methods during PdPR using Quizizz is good and most of them agree with the statements given regarding motivation, learning, teamwork, and learning strategies. Educators  need to be aware of the priority of attracting interest and acceptance of students in the integration of technology introduced to increase their involvement in academic activities thus contributing to a good understanding and showing encouraging performance.